Transposing the Tradition: Providing Embedded Reference Service to Music Students. (3rd April 2017) - Woznicki, Lisa M.
ABSTRACT: This article describes a project designed to improve reference service to music students at a large metropolitan university. When faced with student and faculty complaints that the library and its resources were located too far away from the building where music study takes place, the Performing Arts Librarian took services and research assistance directly into the arts building. Focus is given to the design, implementation, and evaluation of the project.